Communication systems : - Carlson, A. Bruce (McGraw-Hill, 1968)
Covers the three major areas: signal and system analysis, analog communication, and digital communication. Emphasis on HDTV, LANs, WANs, satellite (iridium) telephone systems to address changes in professional arena. Features examples and exercises within each chapter, helping to master new concepts as they are introduced.